Association Between Simple Carbohydrate Intake and Menstrual Duration Among Female Medical Students Of The Faculty Of Medicine Muhammadiyah University of North Sumatra - Artika Sari Siregar; Eka Febriyanti (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Menstruation is a physiological process heavily influenced by metabolic and endocrine pathways. Modern dietary shifts, particularly the high intake of simple carbohydrates, can disrupt glucose homeostasis and insulin sensitivity, potentially altering reproductive hormone regulation and menstrual characteristics. This study aims to determine the association between the frequency of simple carbohydrate intake and menstrual duration among female medical students at the Muhammadiyah University of North Sumatra (UMSU). Method: An analytical observational study utilizing a cross-sectional design was conducted with 90 female medical students. Dietary patterns were assessed using a Food Frequency Questionnaire (FFQ) to categorize simple carbohydrate consumption (3x/week vs. 3x/week). Menstrual duration was recorded and categorized as normal (8 days) or prolonged (8 days). Data were analyzed using the Chi-square statistical test. Results: The cohort was predominantly 19 years old. A significant majority of respondents (73.3%, n=66) reported frequent consumption of simple carbohydrates (3x/week). Analysis revealed a statistically significant association between high-frequency simple carbohydrate intake and prolonged menstrual duration (p 0.01). All respondents in the infrequent consumption group (3x/week) exhibited normal menstrual duration. Discussion: There is a significant positive association between high dietary intake of simple carbohydrates and prolonged menstrual bleeding duration. These findings underscore the critical need for nutritional education emphasizing glycemic control to support reproductive health in young adult women.